Target azimuth estimation in the presence of linear array shape distortion - Wenquan Zhai; Jian Li; Kai Xie (2015 8th International Congress on Image and Signal Processing (CISP), 2015)
The array shape distortion effect on soft linear array Direction of Arrival (DOA) estimation performance was studied by theory analysis, simulation and field data process. The steering vector of beamforming algorithm was mismatched when array shape was distorted, then cause the line array direction performance degradation even failure. Our analysis based conventional beamforming(CBF) and adaptive beamforming (ABF) algorithm. The paper first derived the general arbitrary array beamforming algorithm, introduced how the beamforming steering vector was influenced by the array shape distortion. Secondly, we proved the analysis through simulating and field data processing. At last, the result and conclusion shows that: (1). When shape distortion, performance of both CBF and ABF degradation clearly, CBF is more robust than ABF method; (2). theaccuracy of DOA estimation output and the 3dB width of main lobe have been significantly improved after appropriate array shape distortion adjustment.